A systematic review on semantic-based ontology for Quranic knowledge - Rusli A.S.M.; Zaki Z.M.; Salam R.A.; Farida Hazwani Mohd Ridzuan; M. Norazizi Sham Mohd Sayuti (Science Publishing Corporation Inc, 2024)
Indexed by SCOPUS/ERA